Mobile Application – Lose It Together - Teixeira, Bruno Miguel Almeida (2021)
Mobile Applications, while a recent addition to the tools humans use, have a substantial impact on our lives, and whilst most improve them, some can change the lives of its users. Developing a mobile application gets easier every day but innovative ideas require lots of work and research in order to make up for the effort. Lose It Together is a mobile application that aims to bring people together facing similar challenges regarding weight loss. Through its group feature any user can find others within the same age group and with the same weight. Once grouped up, the users can motivate each other, share milestones together, share difficulties faced and offer and receive advice from their peers. This work aims to shows the process from idea to a product (an alpha version) along with the challenges met as well as the solutions engineered to overcome such challenges. Using new but formidable technologies such as Flutter, Firebase and .NET allowed to create an application that offer a smooth experience in all handheld devices, offer scalability which is extremely import for the final product and most important imposed the need to research, learn and apply the knowledge acquired. The group feature is a technical challenge as it must dynamically introduce users in the application pool and find them, as fast as possible, a group while constraint by the user preferences, this problem brushes in the clustering topic mostly known in the machine learning field.